2014
DOI: 10.5153/sro.3230
|View full text |Cite
|
Sign up to set email alerts
|

Positive Sociology and Appreciative Empathy: History and Prospects

Abstract: This paper explores the contributions of sociology (and overlapping disciplines such as anthropology, social policy, and cultural studies) to happiness scholarship from the Enlightenment through to the present day. Pre-20th century thinkers whose work led to the formation of social science tended to take the theme of happiness seriously as a central challenge of social scholarship. Over the past century, sociologists have made important contributions to understanding happiness, although its absence from textbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Whilst it has become customary for proponents of disciplinary turns towards happiness to lament the traditional focus upon pathology, numerous analyses have described how happiness research itself unwittingly propounds negative, problematised images of human beings (Burnett ; Cieslik and Bartram ; Ecclestone ; Held ; Matthews and Zeidner ; Thin ). For instance, Thin (, , ) claims emphasis on problems blinds researchers from considering how people find happiness. ‘Happiness is implicitly assumed to exist in the absence of the various problems […] and the work of promoting mental health is implicitly assumed to be the work of preventing, alleviating and curing mental illness’ (Thin, :13).…”
Section: Diminished Subjectivity and Individualisationmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst it has become customary for proponents of disciplinary turns towards happiness to lament the traditional focus upon pathology, numerous analyses have described how happiness research itself unwittingly propounds negative, problematised images of human beings (Burnett ; Cieslik and Bartram ; Ecclestone ; Held ; Matthews and Zeidner ; Thin ). For instance, Thin (, , ) claims emphasis on problems blinds researchers from considering how people find happiness. ‘Happiness is implicitly assumed to exist in the absence of the various problems […] and the work of promoting mental health is implicitly assumed to be the work of preventing, alleviating and curing mental illness’ (Thin, :13).…”
Section: Diminished Subjectivity and Individualisationmentioning
confidence: 99%
“…1 It has also become an increasingly significant object of public policy both domestically and internationally with governments around the world considering measures of happiness, or 'subjective well-being,' as progress indicators and tools for appraising policy (Helliwell et al 2013;OECD 2013; Parliamentary Office of Science and Technology 2012; Stiglitz et al 2009;UN General Assembly 2011). Responding to these trends, there have been calls for sociologists to contribute to this growing field by producing sociological research on happiness (Bartram 2012;Cieslik and Bartram 2014;Firebaugh and Schroeder 2009;Stebbins 2009;Thin 2012Thin , 2014. It has been suggested that a key benefit of a 'sociological lens' (Thin 2014) would be to refocus analyses away from overly individualistic, biological or otherwise de-contextualised considerations emerging from other disciplines (Bartram 2012;Carlisle and Hanlon 2007;Horwitz 2002;Schnittker 2008;Thin 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, much of the problematisation of happiness is implicit. For instance, Thin (2014) has argued that where psychology and economics have monopolised the happiness industry, social scientists should ‘develop their own ways of paying “positive” attention to the social facilitation of wellbeing’. But if happiness and well-being are not a problem, one wonders why they need to be ‘promoted’ or ‘facilitated’.…”
Section: A Fledgling Master Framementioning
confidence: 99%
“…We believe that academic enquiry has the opportunity -arguably a moral obligation -to deconstruct and contextualize the terminology of operational SDP into the specific workings of complex social and cultural systems. By critically engaging with these understandings through anthropologically sound fieldwork and methods, a humanistic approach to research in the first-person (Thin 2014) is established that allows researchers to engage in a (re)conceptualizing of SDP language from the perspective of the local, not simply recycling assumptions for the sake of academic exercise.…”
Section: Deconstruction Conceptualization and Empowering The 'Local'mentioning
confidence: 99%